Peran Pendidikan Islam dalam Krisis Akademik Mahasiswa Fisika UPI: Orientasi Pahala dan Tuntutan SKS (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
The academic crisis among Physics students often arises due to the pressure of the credit semester sistem (SKS), grade demands, and heavy study loads. This condition drives students to focus solely on achieving academic results, while the essence of learning as worship is often overlooked. This study aims to explore how the values of Islamic education, particularly the orientation towards rewards, can help students cope with academic pressure. The methods used include literature review and a quantitative survey with an online questionnaire completed by 56 Physics and Physics Education students at Universitas Pendidikan Indonesia. The analysis results show a significant correlation between the SKS pressure and changes in learning behavior (r = 0.807), while the orientation towards rewards acts as a spiritual balance. The findings suggest that Islamic education plays a crucial role in building academic resilience through values of sincerity (ikhlas), patience (sabar), trust in God (tawakal), and balance (tawazun). Thus, academic achievements can become a means of worship while contributing positively to society. This study highlights the importance of spiritual values in achieving balanced academic success.